Effectiveness of Mindful Routine in Attention Deficit Hyperactive Disorder (ADHD) Children - Soumyashree Samantaray; Santosh Kumar Singh; Swaroop Patel; Ankita Patel; Dibyendu Roy (Journal of ADHD And Care, 2024)
Attention deficit hyperactive disorder is characterised by set of neurological based symptoms in children which falls into broadly two categories; inattention and hyperactive impulsive behaviour. It adversely affect child in various areas like social skill, communication, routine of daily life, academic performance and many.It not only affects the child but also other family members. ADHD often creates unproductive pattern, spouse conflict and poor quality of life. Because of executive function issue, ADHD child face difficulty in establishing and maintaining routines from morning to night which increase demands on parents. As a result parents becomes more exhausted ,emotionally triggered and breakdown.This study shows establishing consistent mindfulness routine make daily life simpler and easier for both the parent and children with ADHD.
Keywords: ADHD